1973
DOI: 10.1017/s1446788700015457
|View full text |Cite
|
Sign up to set email alerts
|

The representation of d. g. near-rings

Abstract: In this paper we study the problem of the representation of d.g. near-rings, and in particular the problem of a faithful representation, which is equivalent to the adjoining of an identity. This problem has been considered by Malone [5] and Malone and Heatherly [6] and [7]. They have shown that a finite near-ring with two sided zero can be embedded in the d.g. near-ring generated by the inner automorphisms of a suitable group, and that an identity can always be adjoined to a near-ring with two sided zero. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…Jackson and Arundel ( 1971 ) examined a larger sample and found 7.1 % of dogs infected in the western region of Victoria. In reporting progress of the hydatid control scheme in Tasmania, Meldrum and McConnell (1968) reported that the State incidence of infected dogs fell from 11.2% in 1964 to 2.1% in 1967.…”
Section: Straying Infected Dogsmentioning
confidence: 99%
“…Jackson and Arundel ( 1971 ) examined a larger sample and found 7.1 % of dogs infected in the western region of Victoria. In reporting progress of the hydatid control scheme in Tasmania, Meldrum and McConnell (1968) reported that the State incidence of infected dogs fell from 11.2% in 1964 to 2.1% in 1967.…”
Section: Straying Infected Dogsmentioning
confidence: 99%
“…A campaign aimed at reducing the prevalence of Echinococcus granulosus (locally known as the Hydatid Limitation Program) began in Tasmania in 1965 with the annual purging of dogs to identify areas of high prevalence of E. granulosus combined with a strong educational program aimed at breaking the life cycle (Meldrum andMcConnell 1968, Bramble 1974). …”
Section: Introductionmentioning
confidence: 99%
“…For any d.g. near-ring, the free (R, S) group on a set X exists and is denoted ¥r{X, R, S) (Section 2 of Meldrum (2)). If X = {x} is a one element set, we write Fr( In this paper, we consider d.g.…”
Section: Near-ring Then a Dg Homomorphism 6 From (/? S) To (T U)mentioning
confidence: 99%
“…We-remark that we could restrict ourselves to working within a variety "V of additive groups as was done in Meldrum (2), and all the results will go over in such a context. Now assume that the result is true for m = q and let the length of D(U') = q + 1.…”
Section: X R S) For Fr(a" R S) a Group G Is An (R S) Group If Tmentioning
confidence: 99%
See 1 more Smart Citation